AESTHETICS OF PLAK-PLIENG GRAVESTONE OF LAMURI KINGDOM ACEH: A STUDY ACCORDING TO SUSANNE KNAUTH LANGER'S AESTHETIC CONCEPT - Rajes Ikhlas Rosaguna; Mauly Purba; Agus Priyatno (Universitas Negeri Medan, 2024)
The Lamuri Kingdom in Aceh has relics in the form of gravestones called